Functional analysis and characterization of the human RBBP6 promoters based on a combination of molecular biology and in silico approaches provide additional evidence for RBBP6 role in apoptosis - Pretorius, A.; Kaur, M.; Wamalwa, M.; February, M.F.; Essack, M.; Bajic, V.B.; Rees, D.J.G. (2011)
Retinoblastoma Binding Protein 6 (RBBP6) has been implicated in the apoptotic pathway and regulation of the cell cycle through its interaction with p53, Rb and YB1 and ubiquitination of YB1. Analysis of transcripts indicated the existence of two promoters responsible for the regulation of the gene namely Promoter 0 (P0) and Promoter 1 (P1). With a combination of molecular and computational techniques we analysed and functionally characterised these two promoters of the RBBP6 gene. In this study, we demonstrate that the activity of both promoters increase following camptothecin-induced apoptosis, with notable difference in activities of P0 relative to P1, though activities of both have increased. Computational analysis suggests that both P0 and P1 transcription start sites are located within CpG islands, and that P1 has a functional TATAbox contrary to P0. Promoter content analysis further suggested the presence of six-transcription factor binding sites that are common to both promoters and several others unique to each promoter. Functional analysis of all the transcription factors using GO, KEGG and DAVID analysis, associated P0 more strongly with apoptosis, while P1 was associated more with the regulation of the cell cycle. In addition, P1 was also associated with ubiquitin-mediated proteolysis, while both promoters have been associated with the antigen processing and presentation pathway. Although an association between RBBP6 and cancer has already been made, we also found additional associations with diabetes and Alzheimer’s disease. - See more at: http://dl4.globalstf.org/?wpsc-product=functional-analysis-and-characterization-of-the-human-rbbp6-promoters-based-on-a-combination-of-molecular-biology-and-in-silico-approaches-provide-additional-evidence-for-rbbp6-role-in-apoptosis#more-2310